PENGARUH KEPEMIMPINAN DAN PEMBINAAN TERHADAP KINERJA PEGAWAI DI SEKRETARIAT KPU PROVINSI BENGKULU - Hermanu, Rian (Jurnal Governance dan Administrasi Publik, 2018)
This research was carried out to determine the extent of employee work performance at the Secretariat General Electoral Commission of the Bengkulu Province in achieving its intended purposes. This  research used descriptive statistic method with quantitative approach and data collection was obatined  through field research. Some problems could be faced by the employees there are problems of coaching and discipline performance. Therefore, a leader in an organization should have an ability to develop an improvement program for better and qualified employee through coaching all staff. As a leader in an institution, they should be responsible for the implementation of coaching activities and improvement of the employee performance. Based on the research results, it was found out that any correlation value of  the relationship between leadership and coaching to employee performance, it was 0.972 or we can say that intensity of relationship between leadership and coaching was about 97.2%. From this data, we can assume that  leadership and  coaching highly influence to the employee performance. There are still limitations or a deficiency on this research, one of which is limited in taking the research sample where was distributed only to employees in the province of  Bengkulu Electoral Commission Secretariat mean while there are still other larger organizational structures has not been included, so that the level of generalities are still less.